Prinsip-Prinsip Pengembangan Kurikulum Pendidikan Agama Islam Perspektif Islam: Principles of Islamic Religious Education Curriculum Development from an Islamic Perspective - Nurul Zainab (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2017)
The curriculum of Islamic Religious Education (PAI) faces persistent criticism for being overly theoretical, cognitive-oriented, and disconnected from social change, thus failing to produce comprehensive and integrative educational outcomes. This conceptual issue necessitates a return to fundamental principles, particularly those rooted in Islamic sources such as the Qur’an and Hadith. This study aims to identify and analyze the foundational principles of PAI curriculum development from both general and Islamic perspectives. Employing a qualitative library research method, this study examines primary sources including the Qur’an, Hadith, and works of Islamic education scholars, alongside secondary literature on curriculum theory. The findings reveal that while general principles such as relevance, effectiveness, efficiency, continuity, and flexibility are essential, the Islamic perspective introduces distinctive principles including tauhid (oneness of God), integration of spiritual and material dimensions, balance between ethics, logic, and psychomotor skills, lifelong education, and alignment with human fitrah (innate nature). Furthermore, Qur’anic verses (e.g., Al-Mujaadilah: 11, Al-Qashash: 77) and Hadith serve as foundational references. The study concludes that PAI curriculum development must integrate both universal and Islamic-specific principles, producing a holistic, non-dogmatic, and contextually relevant curriculum. Recommendations emphasize adopting an integrative approach, continuous evaluation, and alignment with the ultimate aims of Islamic education: creating faithful, knowledgeable, and morally upright individuals. Kurikulum Pendidikan Agama Islam (PAI) masih menghadapi kritik karena terlalu teoretis, berorientasi kognitif, dan kurang merespons perubahan sosial, sehingga belum menghasilkan capaian pendidikan yang komprehensif dan integratif. Permasalahan konseptual ini memerlukan penguatan prinsip-prinsip dasar, terutama yang bersumber dari al-Qur’an dan Hadis. Penelitian ini bertujuan mengidentifikasi dan menganalisis prinsip-prinsip pokok pengembangan kurikulum PAI perspektif umum dan Islam. Menggunakan metode penelitian kepustakaan kualitatif, sumber data primer meliputi al-Qur’an, Hadis, dan karya tokoh pendidikan Islam, serta literatur sekunder tentang teori kurikulum. Hasil penelitian menunjukkan bahwa selain prinsip umum seperti relevansi, efektivitas, efisiensi, kontinuitas, dan fleksibilitas, perspektif Islam menambahkan prinsip khas yaitu tauhid, integrasi aspek spiritual dan material, keseimbangan etika-logika-kinestika, pendidikan sepanjang hayat, serta kesesuaian dengan fitrah manusia. Ayat al-Qur’an (QS. Al-Mujaadilah: 11, QS. Al-Qashash: 77) dan hadis menjadi rujukan fundamental. Kesimpulannya, pengembangan kurikulum PAI harus memadukan prinsip umum dan Islam secara integratif sehingga menghasilkan kurikulum holistik, tidak dogmatis, dan kontekstual. Rekomendasi penelitian ini adalah perlunya pendekatan integratif, evaluasi berkelanjutan, dan keselarasan dengan tujuan akhir pendidikan Islam, yaitu membentuk manusia beriman, berilmu, dan berakhlak mulia.